Pengaruh Kinerja Keuangan Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia - Anggareni, Ni Putu Dyah; Ni Wayan Alit Erlina Wati; Rai Dwi Andayani W (UNHI Press, 2025)
Financial performance is measured through profitability (ROE), Liquidity (CR), and Leverage (DER). The population in this study is 160 mining sector companies registered on the IDX in 2021-2023. In the sample selection results, there were 46 companies in the 3 years period of observation, a total of 148 issuers studied. And in testing the data was selected again using an outlier test so that the final sample results were 114 issuers studied. The analysis technique used is multiple linear regression analysis. The research results show that Profitability has a positive and significant effect, Liquidity has a negative and significant effect, Leverage has no effect and Company size has no effect on the value of mining sector companies listed on the Indonesia Stock Exchange with an observation period of 2021-2023